DISKRIMINASI ETNIS ROHINGYA OLEH PEMERINTAH MYANMAR DI TENGAH TEKANAN INTERNASIONAL (THE ROHINGYA ETHNIC DISCRIMINATION BY THE GOVERNMENT OF MYANMAR UNDER INTERNATIONAL PRESSURE - Rizki Nanda Apriani (HI 16 UMY 085, 2016)
*85 Ethnic Rohingya be one that is not claimed its existence and discriminated against by the government of Myanmar. Religion identities between Muslim minoritiy and Budhist majority have been made use to raise violence among parties. This paper try to analyze whether the reason the government is still discriminate Rohingya even though the international pressures are high, one of them is the Organisation of Islamic Cooperation (OIC)) and UNHCR (United Nations Highs Commissioner for Refugees). Through literature review, the study results indicate that the reason behind this discrimination in order to pursue their real interests of the domination of power and land ownership and business opportunities (oil and gas). In addition, this study also identifies discriminative policies support by radical Buddhist group. Keywords: Discrimination, ethnic Rohingya